Acompanhamento e avaliação de projetos através da monitoração de eventos em um ambiente de gestão de processos de software - PAXIÚBA, Carla Marina Costa (Universidade Federal do Pará, 2017)
One of the greatest challenges found in software project management nowadays is to know the true dimension of what is being managed. There are several concerns that are relevant to project managers with respect to the estimation of size, duration, and cost of a project. In this context researchs show that the minor part of the projects are completed on time, on budget, and with all the features and functions originally specified. The other projects are completed overbudget, late or fail. Software project and product management can reach a given level of efficacy and exactness only if certain measurements are made in order to make it possible to manage based on facts. This dissertation focuses on efficient project management process which must be guided by the international process improvement standards and through the use of metrics as a fundamental tool for an effective project management. The basic assumption is that, without the use of adequate metrics, the planning and monitoring of projects become empirical activities, based solely on the feeling and experience of the project manager. This work presents a proposal for projects monitoring through the extension of the event recording mechanism of the WebAPSEE process-centered software engineering environment. The mechanism is the base to provide software support to generate monitoring reports based on process improvement approaches like CMMI and the Brazilian MPS.BR. The proposal was evaluated through a critical analysis involving the monitoring of simulated project with the proposed tool.